Problematization of Social Reality in Communicative Practices of Conflict Mobilization in Communities Social Networks in Germany - L. N. Rebrina (Научный диалог, 2021)
The results of studying the subject system-communicative dimension of conflict mobilization practices in social networks in Germany in the context of mediatization of politics and postulates of successful conflict communication of the Harvard School of Conflictology are presented in the article. The spheres of social life, characterized from the perspective of observers — members of mobilization communities — as a concentration of problem situations and phenomena are determined. The fact of achieving the planned impact when problematizing fragments of social reality is confirmed by the predominance of solidarity reactions of the addressees. The conclusion is made about the predominant presentation of fragments of social reality as a threat through a direct assessment, an indication of the need for confrontation as the main task of the community, broad calls for struggle and criticism of the opponent; about the dominant reinforced presentation of the assessment to the addressee. The consequences of modern mediation in the political sphere, which are reflected in the practices of conflict mobilization, including the changing characteristics and attitudes of communicants, are described. Mobilization practices are characterized as the practice of institutionalizing protest and conflict resolution. It is shown that the studied discursive practices combine the features of different conflict resolution strategies, re-veal partial deviations from the postulates of successful conflict communication, formulated by representatives of the Harvard School of Conflictology in the concept of “Principled Negotiations”.